Climate and socio‐economic factors explain differences between observed and expected naturalization patterns of European plants around the world. Issue 7 (31st May 2021) - Pouteau, Robin; Thuiller, Wilfried; Hobohm, Carsten; Brunel, Caroline; Conn, Barry J.; Dawson, Wayne; de Sá Dechoum, Michele; Ebel, Aleksandr L.; Essl, Franz; Fragman‐Sapir, Ori; Fristoe, Trevor; Jogan, Nejc; et al.
Abstract: Aim: The number of naturalized (i.e. established) alien species has increased rapidly over recent centuries. Given the differences in environmental tolerances among species, little is known about what factors determine the extent to which the observed size of the naturalized range of a species and hence the extent to which the observed richness of naturalized species of a region approach their full potential. Here, we asked which region‐ and species‐specific characteristics explain differences between observed and expected naturalizations. Location: Global. Time period: Present. Major taxa studied: Vascular plants. Methods: We determined the observed naturalized distribution outside Europe for 1, 485 species endemic to Europe using the Global Naturalized Alien Flora (GloNAF) database and their expected distributions outside Europe using species distribution models. First, we investigated which of seven socio‐economic factors related to introduction pathways, anthropogenic pressures and inventory effort best explained the differences between observed and expected naturalized European floras. Second, we examined whether distributional features, economic use and functional traits explain the extent to which species have filled their expected ranges outside Europe. Results: In terms of suitable area, more than 95% of expected naturalizations of European plants were not yet observed. Species were naturalized in only 4.2% of their suitable regions outside of Europe (range filling) and in 0.4% of their unsuitable regions (range expansion). Anthropogenic habitat disturbance primarily explained the difference between observed and expected naturalized European floras, as did the number of treaties relevant to invasive species. Species of ornamental and economic value and with large specific leaf area performed better at filling and expanding beyond their expected range. Main conclusions: The naturalization of alien plant species is explained by climate matching but also by the regional level of human development, the introduction pressure associated with the ornamental and economic values of the species and their adaptation to disturbed environments.